2022
DOI: 10.1038/s41598-022-05661-6
|View full text |Cite
|
Sign up to set email alerts
|

Syntax errors do not disrupt acoustic communication in the common cuckoo

Abstract: When acoustic communication signals are distorted, receivers may misunderstand the signal, rendering it ineffective. Common cuckoos (Cuculus canorus) are popularly known for the males’ simple, two-note advertisement calls, the “cu-coo” used for declaring the male’s breeding territories. Cuckoos do not learn their calls (vocal non-learners), so they are expected to have a limited ability to produce different acoustic signals. Nevertheless, male cuckoos appear to make syntax errors (e.g., repeated, reversed, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…However, Wang Y. et al found no evidence that these calls affected host response and was insufficient for suppressing bird activities. Unlike female cuckoo vocalizations, male cuckoo calls do not have any apparent role in countering host defenses and instead are sexually selected (Moskát et al, 2017;Moskát and Hauber, 2022). Esposito et al analyzed acoustic variables and visual display sequences of male common cuckoos to determine whether these signals are multimodal by nature and complement one another as is known to occur in other brood parasites (O'Loghlen and Rothstein, 2010).…”
Section: Editorial On the Research Topic Evolution And Function Of Ac...mentioning
confidence: 99%
“…However, Wang Y. et al found no evidence that these calls affected host response and was insufficient for suppressing bird activities. Unlike female cuckoo vocalizations, male cuckoo calls do not have any apparent role in countering host defenses and instead are sexually selected (Moskát et al, 2017;Moskát and Hauber, 2022). Esposito et al analyzed acoustic variables and visual display sequences of male common cuckoos to determine whether these signals are multimodal by nature and complement one another as is known to occur in other brood parasites (O'Loghlen and Rothstein, 2010).…”
Section: Editorial On the Research Topic Evolution And Function Of Ac...mentioning
confidence: 99%